2021
DOI: 10.3390/ijerph18073367
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Willingness and Impact of the COVID-19 Pandemic on Women’s Perinatal Experiences and Practices—A Multinational, Cross-Sectional Study Covering the First Wave of the Pandemic

Abstract: The COVID-19 pandemic may be of particular concern for pregnant and breastfeeding women. We aimed to explore their beliefs about the coronavirus and COVID-19 vaccine willingness and to assess the impact of the pandemic on perinatal experiences and practices. A multinational, cross-sectional, web-based study was performed in six European countries between April and July 2020. The anonymous survey was promoted via social media. In total, 16,063 women participated (including 6661 pregnant and 9402 breastfeeding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
120
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 40 publications
8
120
0
Order By: Relevance
“…Although not statistically significant, women with an associate's degree or higher were more willing to receive the COVID-19 vaccine when compared to women with a high school education or less. This result is consistent with a study discussed in Ceulemans et al (6), which reported that pregnant and breastfeeding women with low to medium education levels were less likely to get the COVID-19 vaccine when it became available to them. Similarly, unemployment was associated with vaccine hesitancy.…”
Section: Conclusion/discussionsupporting
confidence: 92%
“…Although not statistically significant, women with an associate's degree or higher were more willing to receive the COVID-19 vaccine when compared to women with a high school education or less. This result is consistent with a study discussed in Ceulemans et al (6), which reported that pregnant and breastfeeding women with low to medium education levels were less likely to get the COVID-19 vaccine when it became available to them. Similarly, unemployment was associated with vaccine hesitancy.…”
Section: Conclusion/discussionsupporting
confidence: 92%
“…In the literature of the subject, various attitudes regarding willingness to get vaccinated can be noticed and the willingness ranges from 40% to 94% of the respondents, depending on the country [20,21]. Among others, a survey conducted in six European countries: Ireland, Norway, Switzerland, the Netherlands, Great Britain and Belgium, among pregnant or breastfeeding women indicates 40-50% willingness to undergo vaccination depending on the country [22]. Surprisingly, in the literature, there are downward trends observed as the pandemic continues and such a correlation has been observed, i.e., in the USA, where there was a decline of support toward vaccination from 76% in April 2020 to 56% in December 2020, despite numerous positive information regarding the effectiveness of the preparations [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature of the subject, various attitudes regarding willingness to get vaccinated can be noticed and the willingness ranges from 40% to 94% of the respondents, depending on the country [ 20 , 21 ]. Among others, a survey conducted in six European countries: Ireland, Norway, Switzerland, the Netherlands, Great Britain and Belgium, among pregnant or breastfeeding women indicates 40–50% willingness to undergo vaccination depending on the country [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal was to examine the overall impact of the SARS-CoV-2 pandemic on pregnant and breastfeeding women (i.e., pregnancy/breastfeeding experience, life and professional habits, mental health status, relationship with the healthcare system, medication use, and vaccine perceptions during pregnancy/breastfeeding) [ 24 ]. The COVID-19 vaccine willingness of pregnant and breastfeeding women included in the multi-center study has already been published [ 25 ], and the Swiss rate was among the lowest, hence the need to investigate the factors associated with vaccine acceptance in a Swiss-specific study.…”
Section: Methodsmentioning
confidence: 99%